The Effect of Job Placement and Workload on Work Motivation In Cv. Ibnu Aqil Mandiri Lubuk Pakam - Henny Purnama Dewi (Jurnal Mantik, 2022)
The phenomenon has been the author observed in the CV. Ibnu Aqil Mandiri Lubuk Pakam include staffing are not in accordance with the demands of office and educational background, so do not meet the capacity capability as it should be. Needs of employees who are competent in accordance with his position is not sufficient consequence less attitude responsible for the work, motivation for achievement is lost, do not feel like working and feeling saturated. The purpose of this research was to determine the effect of employment and workload on work motivation at CV. Ibnu Aqil Mandiri Lubuk Pakam. The method used is multiple linear regression. The results showed that together the variables of employment and workload significant effect on work motivation. Values ??X1 < ttable (1,471 <2,004), so it is stated that employment does not significantly influence the work motivation. As for X2 > ttable (3,198> 2,004), it also means that the workload of a significant effect on work motivation.